Verbalization of the “threat” concept in the Russian language - Ushakova E. V. (Interactive science, 2017)
the author examines the “threat” concept in the Russian language, as well as provides the main goal of the work – to describe the “threat” concept as one of the types of a conflict manifestation.
Keywords: концепт; конфликт; угроза; понятие; concept; когнитивная структура; conflict; notion; threat; cognitive structure